Lex Imperfecta of Language Obligation and Conditioned Contracts - Zain, Ilham Muhammad; Surya Kusuma, Febrian Indar (Kadiri Islamic University, 2025)
This study examines the fundamental paradox within the Indonesian legal regime arising from Article 31 paragraph (1) of Law Number 24 of 2009 on the Flag, Language, State Emblem, and National Anthem which mandates the use of the Indonesian language in agreements involving Indonesian parties yet provides no sanction mechanism for its violation. This condition renders the norm a lex imperfecta, a formally existing obligation that lacks coercive force, leaving linguistic sovereignty as an aspiration without real enforcement. The research employs a normative juridical method combining statutory and conceptual approaches, analyzing primary legal materials including the Civil Code, Law Number 24 of 2009, and relevant Supreme Court instruments. This study finds that the absence of sanctions generates two concurrent pathologies: at the theoretical level a normative vacuum undermines legal system coherence, and at the practical level it produces massive judicial disparity in the treatment of foreign language contracts. The institutional response through Supreme Court Circular Letter Number 3 of 2023 which introduces the criterion of bad faith as a threshold for contract cancellation lacks textual grounding in the law itself and constitutes an informal constitutional bypass exceeding judicial authority. This study proposes a legislative reform adopting two complementary frameworks, namely the doctrine of unenforceable contracts which distinguishes between void and suspended agreements, and the concept of Linguistically Conditioned Contracts wherein foreign language agreements remain legally recognized but their enforceability is suspended until language obligations are fulfilled within a court determined deadline. This framework upholds linguistic sovereignty as a valid public norm while preserving civil law certainty as the foundation of modern economic transactions.